Trauma and belief systems; an operational code analysis of Dutch Prime Minister Rutte and the downing of flight MH17. Issue 2 (2nd March 2021) - Willigen, Niels van; Bakker, Femke E.
Abstract: What is the impact of a crisis on the belief systems of leaders? We know from a substantial body of research that the beliefs of leaders impact their decision making processes. These beliefs are generally assumed to be stable, which makes them a reliable tool for explaining decision making behavior. There is, however, some limited evidence that suggests that when crises are experienced by leaders as a traumatic event, their beliefs can be affected. This article studies the potential impact of crisis‐induced trauma on leaders' belief systems by measuring the operational codes of Dutch Prime Minister Mark Rutte before and after the shooting down of flight MH17 in 2014 in Ukraine. We use quantitative content analysis of written texts such as the speeches by Rutte. Our aim is to contribute to the crisis management literature that focuses on individual leadership and crises by finding out whether Rutte's operational code changed significantly after the downing of flight MH17. We conclude that there were two significant changes in Rutte's belief system, but these cannot be attributed to the effects of the traumatic event only. Therefore we offer an alternative explanation that combines the traumatic event hypothesis with the crisis‐learning hypothesis. 摘要: 一场危机对领导者信念体系产生的影响是什么？从大量研究中我们了解到，领导者的信念会影响其决策过程。这些信念一般被认为是稳定的，因此是用于解释决策行为的可信赖工具。然而，相当有限的证据暗示，当危机被领导者认为是一场创伤性事件时，其信念可能会受到影响。通过衡量有关2014年MH17客机在乌克兰坠毁前后荷兰首相马克·吕特的操作码，本文研究了因危机产生的创伤对领导者信念体系产生的潜在影响。我们对例如吕特的演讲等书面文本使用定量内容分析。我们旨在通过发现吕特的操作码是否在MH17坠毁后发生了显著变化，进而对聚焦于个体领导力和危机的危机管理文献作贡献。我们的结论认为，吕特的信念体系中出现了两次显著变化，但这不能仅归因于创伤性事件造成的影响。因此，我们提供一项将创伤性事件假设和危机学习假设相结合的替代性解释。 Resumen: ¿Cuál es el impacto de una crisis en los sistemas de creencias de los líderes? Sabemos por un cuerpo sustancial de investigación que las creencias de los líderes impactan sus procesos de toma de decisiones. En general, se asume que estas creencias son estables, lo que las convierte en una herramienta confiable para explicar el comportamiento de toma de decisiones. Sin embargo, hay algunas pruebas limitadas que sugieren que cuando los líderes experimentan las crisis como un evento traumático, sus creencias pueden verse afectadas. Este artículo estudia el impacto potencial del trauma inducido por la crisis en los sistemas de creencias de los líderes midiendo los códigos operativos del primer ministro holandés Mark Rutte antes y después del derribo del vuelo MH17 en 2014 en Ucrania. Utilizamos análisis de contenido cuantitativo de textos escritos como los discursos de Rutte. Nuestro objetivo es contribuir a la literatura de gestión de crisis que se centra en el liderazgo individual y las crisis al descubrir si el código operativo de Rutte cambió significativamente después del derribo del vuelo MH17. Concluimos que hubo dos cambios significativos en el sistema de creencias de Rutte, pero estos no pueden atribuirse únicamente a los efectos del evento traumático. Por tanto, ofrecemos una explicación alternativa que combina la hipótesis del evento traumático con la hipótesis del aprendizaje de crisis.